2020
DOI: 10.3390/app10238511
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis-Based Blast Resistance Performance Assessment of Cable-Stayed Bridge Components Subjected to Blast Loads

Abstract: Cable-stayed bridges are infrastructure facilities of a highly public nature; therefore, it is essential to ensure operational safety and prompt response in the event of a collapse or damage, which are caused by natural and social disasters. Among social disasters, blast accidents can occur in cable-stayed bridges as a result of explosions produced by vehicle collisions or terrorist attacks; this can lead to the degradation in their structural performances and subsequent collapse. In this research, a procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The study in [8] focuses on cable-stayed bridges under blast accidents resulting from explosions produced by vehicle collisions or terrorist attacks. An efficient procedure to assess structural blast-resistance performance of key structural components in cable-stayed bridges is suggested, based on a numerical analysis approach.…”
Section: Contentsmentioning
confidence: 99%
“…The study in [8] focuses on cable-stayed bridges under blast accidents resulting from explosions produced by vehicle collisions or terrorist attacks. An efficient procedure to assess structural blast-resistance performance of key structural components in cable-stayed bridges is suggested, based on a numerical analysis approach.…”
Section: Contentsmentioning
confidence: 99%
“…Therefore, it was necessary to apply some energy absorbing or properly fused systems to reduce the close-in deck explosion effects. Lee and Choi et al [8] suggested a procedure to assess structural blast-resistance performance based on a numerical analysis approach.…”
Section: Introductionmentioning
confidence: 99%
“…In the last six decades, more than 550 terrorist attacks have targeted bridges and related infrastructure [1]. Cable-stayed bridges, being vital public infrastructure, require protection to ensure operational safety and prompt response during natural disasters or intentional acts of destruction, such as explosions resulting from vehicle collisions or terrorist attacks [2]. Protecting cable-stayed bridges against progressive failure due to explosive threats was investigated [3].…”
Section: Introductionmentioning
confidence: 99%